Knowledge based restructuring in transition economies: The role of business environment, competition and ICT - Branko Radulovic (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
The knowledge based restructuring is taking into account the fact that after the inclusion of new entrants, ICT based changes are not solely related to the concept of the strategic restructuring of already existing companies. Using the BEEPS 2 data, we find that new firms and exporters are driving the innovation process in the transition economies and that both the availability of ICT and the existence of competitive pressure raise innovation. In addition, favourable business environment is an important positive determinant of the decision to innovate. Business environment indirectly, through strategic restructuring affects sales growth as strategic restructuring represents positive and significant determinant of the performance ICT both directly and indirectly affects performance equation. Subsidies are weakly positively related to knowledge based restructuring. The question of subsidies needs to be more analysed. It is unclear whether subsidies are now becoming more related to the strategic restructuring through a governmental support to certain industrial sectors, or subsidies are linked to defensive restructuring, as a support to deal with redundancies.
Keywords: 330; Organisatorischer Wandel; Informationstechnik; Institutionelle Infrastruktur; Wettbewerb; Transformationsstaaten